Modeling and Control of Anti-Rolling Gyro System to Stabilize Single-Track Vehicle - Buntheng Chhornand; Unggul Wasiwitono (IPTEK Journal of Proceedings Series, 2020)
Two-wheeled vehicle has many advantages such as small size, more efficiency, and more maneuverable. These advantages come at the lack of stability and safety. To improve the stability and safety of a two-wheeled vehicle, the Control Moment Gyroscopic Stabilization is considered. This system is composed to generate counteracting roll stabilizing torque. In this study, the system of gyroscopic stabilizer is simulated and validated to be implemented into a two-wheeled vehicle. Proportional-Integral-Derivative (PID) controller is designed to control the gimbal for generating the balancing torque. The performance of the proposed controller is evaluated through simulation for non-linear cases. The result of the non-linear model confirms a good balance in terms of rapid response.